DESIGN AND CONSTRUCTION OF A DIAGNOSTIC PULSED X-RAY TUBE - Ibrahim, Mohamed (Al-Nahrain Journal of Science, 2018)
A pulsed X-ray Tube based on the field emission cold cathode principle has been designed andconstructed. The device produced X- ray pulses of duration of (1.2) μ sec and intensities of (90) mRat a distance of (10) cm from the window, when a (150) KV is discharged across the electrodes ofthe tube. The intensity of the x ray radiation at various distances was determined at various cathodeanode spacing to determine its optimum value. Special efforts were made in the design to bedemountable, easy to maintain, and offering a practical possibility for future industrial and medicalapplication